DEFORMABILITY OF BLANKS IN CONDITIONS OF COMPLEX LOADING - Nakhaychuk, O.V.; Pukhtytska, N.O. (Problems of Tribology, 2015)
The tendency of the evaluation of maximum forming of purveyances in the conditions of the difficult loading and unmonotonous deformation are resulted in work. It is rotined that on the basis of development of mathematical theory of plasticity and phenomenological theory is possible prognostication of technological heredity of purveyances without the leadthrough of labour intensive experimental researches